"Minimalist" Dance, Social Critique: Revisiting Yvonne Rainer and Steve Paxton's 1963 Word Words. Issue 3 (21st December 2018) - Morse, Meredith
Abstract : In this essay, I reexamine Yvonne Rainer and Steve Paxton's 1963 dance Word Words, arguing that this apparently "minimalist" work in fact deployed "underground" strategies, those of female (and male) impersonation. Camp performance, an approach that Rainer soon disavowed, allowed Word Words to explore gender in ways that were not possible by the time Rainer developed Trio A . Word Words did not simply "overwrite" Rainer's (female) gender, as has been suggested alongside similar discussions of Trio A and gender, but destabilized the gender system's binaries: a deeply radical move, even in the context of other Judson performances using camp.